A new species of Selenipedium (Orchidaceae: Cypripedioideae) from Ecuador - Cribb, Phillip; Schiuteman, André (Lankesteriana: International Journal on Orchidology, 2015)
A new species of Selenipedium (Orchidaceae: Cypripedioideae) from northern Ecuador is described here and its affinities are discussed. A key to the known species of the genus is provided.